2020
DOI: 10.1371/journal.pone.0242962
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of the Da Qing diabetes prevention program: A modelling study

Abstract: Objective The Da Qing Diabetes Prevention program (DQDP) was a randomized lifestyle modification intervention conducted in 1986 for the prevention and control of type 2 diabetes in individuals with impaired glucose tolerance. The current study estimated long-term cost-effectiveness of the program based on the health utilities from the Chinese population. Methods A Markov Monte Carlo model was developed to estimate the impact of the intervention from the healthcare system perspective. The analysis was run ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…A study demonstrated that age and monocyte–lymphocyte ratio may predict imaging progression on chest CT in COVID-19 patients [ 34 ]. Other studies indicated moderate positive correlations between CT severity score and transferrin, lactate dehydrogenase, troponin, and inflammation-related factors of leucocytes, neutrophils, and IL-2R ( r range 0.45–0.60) [ 17 , 35 ], although we were unable to verify those correlations due to lack of data.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A study demonstrated that age and monocyte–lymphocyte ratio may predict imaging progression on chest CT in COVID-19 patients [ 34 ]. Other studies indicated moderate positive correlations between CT severity score and transferrin, lactate dehydrogenase, troponin, and inflammation-related factors of leucocytes, neutrophils, and IL-2R ( r range 0.45–0.60) [ 17 , 35 ], although we were unable to verify those correlations due to lack of data.…”
Section: Discussionmentioning
confidence: 68%
“…Other studies applied crude CT scoring systems. For example, Wang et al used 0:0%; 1:1–49%; 2:50–75%; 3: > 75%; range 0–3; global score 0–15 [ 16 ]; Hu et al used 0:0%; 1:1–25%; 2:26–50%; 3:51–75%; 4:76–100%; range 0–4; global score 0–20 [ 17 21 ]; Francone et al used 0:0%; 1: < 5%; 2:5–25%; 3:26–50%; 4:51–75%; 5: > 75%; range 0–5; global score 0–25 [ 22 , 23 ]; Zhao et al used 0:0%; 1: < 25%; 2:25–49%; 3:50–74%; 4: ≥ 75%; range 0–4; global score 0–24 [ 24 26 ]; Aalinezhad et al used another system (0:0%; 1: < 50%; 2: > 50%; range 0–2; global score 0–40) [ 27 , 28 ]. Similarly, Guillo et al used a scoring system of 0–10%, 11–25%, 26–50%, 51–75% and 76–100% ground-glass opacities and consolidation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no studies were identified through forward and backward searches. Finally, 11 articles met the selection criteria and were included in the review (see Figure 1 for the PRISMA flow diagram) [ 41 , 42 , 43 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted in Bangladesh [ 48 ], China [ 47 , 52 ] including Hong Kong [ 51 ], India [ 41 , 43 , 49 ], Malaysia [ 54 ], Singapore [ 42 , 50 ], and Sri Lanka [ 53 ] with T2DM patients and participants who were at high risk of developing T2DM. Participants included in the studies were aged 5 years and above, and the average sample size of the studies was 920 participants (study samples ranged between 166 and 3539 participants).…”
Section: Resultsmentioning
confidence: 99%